Kinerja Pelayanan Air Bersih Berbasis Masyarakat di Tugurejo Kota Semarang - Yuliani, Yani; Rahdriawan, Mardwi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
PDAM water service by only 50 % to 10 % for urban and rural, to accelerate the fulfillment of the need for clean water, need to involve the private sector and communities. This study aims to assess the performance of community-based water services in Tugurejo. Analysis of performance in terms of aspects operational, finance, administration and customer satisfactio. The method of research used is a mixture methods (mixed methods), which combines the methods, techniques of data collection, and quantitative and qualitative data analysis. The results of the performance evaluation study covers aspects operasioanl organizers, finance and administration assessed predicate 'good', and "Developing Capable", means they were able to maintain the consistency and quality of water, capable of generating a profit to run operations, maintain the assets, pay the loan obligations; and managers are able to maintain the sustainability of water services to customers. Performance assessment of the customer, customer satisfaction was assessed by the quality of water services. The value of customer satisfaction index (Customer statisfaction Index) is 78.34 % in the category of "satisfied", meaning that almost all customers satisfied with the service quality attributes of water service providers, although not all of the appropriate customer expectations.